Do tax havens create firm value? - Choy, Siu Kai; Lai, Tat-Kei; Ng, Travis (Journal of Corporate Finance, 2017)
On October 11, 2011, a non-governmental organization called ActionAid published a report condemning the FTSE 100 firms for holding an unusually large number of subsidiaries in tax havens. Urging the government to implement appropriate actions, the report raised the firms' costs of holding tax haven subsidiaries. After this event, the stock prices of the nonfinancial firms experienced a 0.9% abnormal drop (corresponding to about £9billion in market capitalization). Those better-governed firms and those with larger shares of subsidiaries in tax havens experienced larger drops. We find some evidence that government scrutiny, reputation, and investor sentiment were plausible channels of such a negative impact.